2010
DOI: 10.1111/j.1440-1819.2010.02131.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and related factors among cancer caregivers in China

Abstract: Aims: The present study was designed to investigate quality of life (QOL) among caregivers of cancer inpatients, and to explore the related factors with the long-term goal to improve QOL of cancer caregivers in China. Methods:A cross-sectional study was performed during the period January-March 2008. Subjects comprised 358 caregivers of cancer inpatients. The questionnaires pertaining to QOL, sociodemographic characteristics, caregiving demands, available social resources, caregiving situation, and caregiver's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
3
23
1
1
Order By: Relevance
“…The Cronbach alpha correlation coefficient for scale and subscales in the culturally adapted FAMCARE scale was high, but in light of the eigen values of this scale, it was decided that a onedimensional scale might be formed from the 20 items with satisfactory reliability, which support the conclusion drawn by other researchers [21,24]. The construct validity of the Quality of Life Scale (Family Version) was confirmed in the study performed by Lu et al [22], but both the order of the factor loading and the content of the subscales were affected in our study. Low factor loading was found for items 5, 6, 23, 30, 31, 32 and 34, suggesting that these seven items are not really measuring the QOL of the caregivers because of the protective and tolerant attitude of the caregivers toward the disease.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The Cronbach alpha correlation coefficient for scale and subscales in the culturally adapted FAMCARE scale was high, but in light of the eigen values of this scale, it was decided that a onedimensional scale might be formed from the 20 items with satisfactory reliability, which support the conclusion drawn by other researchers [21,24]. The construct validity of the Quality of Life Scale (Family Version) was confirmed in the study performed by Lu et al [22], but both the order of the factor loading and the content of the subscales were affected in our study. Low factor loading was found for items 5, 6, 23, 30, 31, 32 and 34, suggesting that these seven items are not really measuring the QOL of the caregivers because of the protective and tolerant attitude of the caregivers toward the disease.…”
Section: Discussionsupporting
confidence: 55%
“…The test-retest reliability was 0.89, and the internal consistency alpha was 0.69 [16]. However, in the study performed by Lu et al, the confirmatory factor analysis and internal consistency of this scale confirmed the construct validity of the questionnaire [22].…”
Section: Instrumentsmentioning
confidence: 81%
See 2 more Smart Citations
“…Other studies, which focused on the QOL of caregivers of cancer patients in different phases of illness, found that the psychological component of their QOL is mainly impacted (Kitrungrote and Cohen, 2006;Kim and Given, 2008;Weitzner et al, 1999;Alptekin et al, 2010;Grunfeld et al, 2004). However, Lu et al (2010) reported that both psychological and social well-being were worse than physical and spiritual well-being. Furthermore, our findings suggest that it is not necessarily the specific characteristics associated with the illness that impact QOL but rather the presence of the illness itself.…”
Section: Discussionmentioning
confidence: 92%